Pengaruh Team based Project pada Pembelajaran Sulaman terhadap Motivasi Belajar Mahasiswa - Vina Oktaviani; Rafikah Husni; Puspaneli Puspaneli; Hazevi Atila Yazel Aze (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Embroidery learning in fashion design education requires technical mastery, creativity, perseverance, collaboration, and the ability to produce aesthetically valuable products. However, student motivation often decreases when practical learning is dominated by lecturer explanation and imitation of examples. This study aims to determine the effect of Team-based Projects in embroidery learning on student learning motivation. A quantitative approach was employed using a quasi-experimental pretest-posttest control group design. The sample consisted of 60 students divided into an experimental class and a control class. The experimental class received team-based project learning, while the control class followed conventional individual practice. Data were collected using a learning motivation questionnaire based on intrinsic motivation, extrinsic motivation, and amotivation. The data were analyzed through normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and simple linear regression. The findings showed that the experimental class’s motivation score increased from 67.83 to 82.37 after the treatment. The independent sample t-test revealed a significant difference between the experimental and control classes, with a p-value < 0.001. Regression analysis also confirmed that Team-based Projects positively affected student learning motivation. These results indicate that team based embroidery projects create more meaningful, collaborative, and challenging learning experiences.